An Empirical Evidence of Energy Consumption and Economic Development Dynamics in Nigeria: What is the Role of Population? - OGBEIDE-OSARETIN, Evelyn Nwamaka; ORHEWERE, Bright (Energy Economics Letters, 2022)
The place of population growth in the linkage between the consumption of energy and economic development in Nigeria was examined in this study. Annual data on total consumption of energy, the growth of population, and economic development were employed among other variables for the time 1995 to 2019. We used Autoregressive Distributed Lag -Error Correction Model (ARDL-ECM). Energy consumption had a feedback negative substantial relationship with economic development in the long run while in the short run, energy consumption had a negative significant impact on economic development. The population growth had a negative significant impact on economic development, and a positive substantial effect on energy consumption. However, energy consumption is not impacted on by oil price. Consequently, we advocate for the increase in the quality of energy, increasing government expenditure in the provision of energy supply, and the population maximization of energy for the achievement of economic development in Nigeria.